2017
DOI: 10.1186/s13104-017-3054-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of electronic reminders and group bonuses on the recording of diagnoses in primary care: a longitudinal follow-up study

Abstract: ObjectiveTo improve the recording of diagnoses in visits to general practitioners, an observational retrospective study based on a before-after design was performed by installing an electronic reminder in the computerized patient chart system, reinforced in feedback delivered in superior-subordinate or development discussions with the general practitioners. The monthly rate of recording diagnoses was observed before and after the intervention. The effect of this intervention on recording of diagnoses was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…GFS provided a specific place in the EHR where the appropriate diagnosis codes of the 10 th version of the International Classification of Diseases (ICD-10) could be entered during the patients’ visits to the doctors of the ED and GPs. The system assisted the doctors in finding a proper diagnosis code or allowed the doctor to use the right code for the desired diagnosis directly, as described in detail earlier [ 10 , 11 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GFS provided a specific place in the EHR where the appropriate diagnosis codes of the 10 th version of the International Classification of Diseases (ICD-10) could be entered during the patients’ visits to the doctors of the ED and GPs. The system assisted the doctors in finding a proper diagnosis code or allowed the doctor to use the right code for the desired diagnosis directly, as described in detail earlier [ 10 , 11 ]…”
Section: Methodsmentioning
confidence: 99%
“…After that time, the reminders were always active till the end of the follow-up period (December 2014). The GFS-system prompted the ED doctors to enter a diagnosis every time they wanted to close a case [ 10 , 11 ] The follow-up period started in February 2002 and ended in December 2014. In February 2015, the primary care ED was totally outsourced to Helsinki University Hospital (HUS) due to a general restructuring of the local ED system in the HUS-area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One important function of electronic reminders is the improvement of the quality of documentation in EDs [ 8 ]. Having recently observed that electronic reminders are effective in increasing the recording rate of diagnoses in ordinary visits of primary care physicians [ 9 , 10 ], it is important to study the association of electronic reminders with documentation in an ED setting. We studied changes in the diagnosis recording rate in a primary health care ED which provides care for unscreened emergency patients in its service area [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this small-scale pilot study, electronic reminders seemed to improve the recording of diagnoses. 7 The aim of this study was to explore whether the electronic reminders within the electronic health record system increased the rate of recording disease diagnoses during GPs' visits. We also wanted to explore which diagnoses were recorded to find out whether the present intervention produced data which reflected the distribution of diagnoses in real clinical life in primary care.…”
Section: Introductionmentioning
confidence: 99%